Update on biological, social and economical aspect of Alzheimer's diasease and other dementia - Trtica-Majnarić, Ljiljana (Array, 2009)
Alzheimer's disease is the most common cause of dementia, accounting for approximately 2/3 of all cases of dementia. The rest includes, in almost equal proportions, vascular dementia and other types of dementia (Table 1). Although different types of dementia can be distinguished according to specific symptom patterns and microscopic brain abnormalities (on autopsy), there is a large range of overlap between them. This can further be complicated by coexisting medical conditions, such as depression and disorders of vascular origin, frequently occurring in people at advanced age. So, pure forms of dementia rarely exist and most cases reflect mixed underlying clinical conditions, but all result in progressive damaging of brain cells and more or less unique pathologic features. It is estimated that dementia affects more than 35 million people worldwide